EXTRACTION OF COPPER AND SILVER DISUBSTITUTED BENZOYLTHIOUREAS - Anaya M., Fernando (2002)
The 1,1 biphenyl-3 - benzoylthiourea(BFBTU) and 1, 1- biethyl - 3- benzoylthiourea (DEBTU), solubilized in chloroform were evaluated as extractanT of metallic ions Cu(II) and Ag(I) aproximatelly 0,01 M, because they form stable chelats with high extraction capacity, particularly when the pH is increased. The higher extraction of Ag(I) compared with Cu(II) for both ligands is because the markedly preference of the S donor atom for Ag(I) ion.